The city in the Islamic world - Holod, Renata.; Jayyusi, Salma Khadra.; Petruccioli, Attilio, 1945-; Raymond, André. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2008)
The purpose of this book, is to draw attention to the sites of life, politics and culture where current and past generations of the Islamic world have made their mark. Unlike many previous volumes dealing with the city in the Islamic world, this one has been specially expanded not only to include snapshots of historical fabric but also to deal with the transformation of this fabric into modern and contemporary urban entities.